Efeito de cultivares de algodoeiro sobre a biologia e capacidade predatória de Orius Insidiosus (say, 1832) (hemiptera: anthocoridae) predando Aphis Gossypii Glover, 1877 (Hemiptera: Aphididae) - Oliveira, J.E.M.; de Bortoli, S.A.; dos Santos, R.F.; Silveira, L.C.P. (My University, 2008)
The objective of this research was to determine the survival, reproduction and predaceous capacity of Orius insidiosus on cotton aphid Aphis gossypii. Cotton plants of Antares, CNPA7H and Acala 90 cultivars (respectively, without tricome, medium tricome density and high tricome density) were individualized and infested with 15 third/fourth instar nymphs of A. gossypii, and then first-instar nymphs of O. insidiosus were released on the plants. The evaluations were made daily, quantifying survival and nymphal development; the number of cotton aphids A. gossypii per day and total; the number of eggs and the population of the predator (number of insects by female); and the conversion efficiency of A. gossypii predaceous. The nymphal development did not differ according to the cotton cultivars. The Antares cultivar favored a higher daily predation rate for the 1st, 2nd and 4th instars and adults of O. insidiosus. The number of eggs and nymphs was smaller when O. insidiosus females were confined on the Acala 90 cultivar. According to the predation rate of O. insidiosus, the efficiency of alimentary conversion was determined for the Antares, CNPA7H and Acala 90 cultivars, being respectively, 4.28, 3.00 and 2.75 cotton aphid predation for each egg of the predator.

Estudou-se a sobrevivência, a reprodução e a capacidade predatória de Orius insidiosus (Say) sobre o pulgão do algodoeiro Aphis gossypii Glover. Plantas de algodoeiro das cultivares Antares, CNPA7H e Acala 90 (respectivamente, glabra, de média pilosidade e pilosa) foram individualizadas e infestadas com quinze ninfas de terceiro/quarto estádio de A. gossypii e, em seguida, liberadas ninfas do predador O. insidiosus a partir do primeiro estádio ninfal.As avaliações foram realizadas diariamente, quantificando-se sobrevivência e desenvolvimento ninfal; o número de pulgões predados por dia e total; o número de ovos e a população do predador (total de indivíduos gerados pelas fêmeas) e determinada a eficiência de conversão alimentar através da taxa de predação de O. insidiosus. O desenvolvimento ninfal não foi afetado pelo cultivar de algodoeiro. O cultivar Antares favoreceu maior taxa diária de predação para os dois primeiros e quarto estádio ninfal e fase adulta de O. insidiosus. O número de ovos e de ninfas foi menor quando as fêmeas de O. insidiosus foram confinadas no cultivar Acala 90. A eficiência de conversão alimentar nos cultivares Antares, CNPA7H e Acala 90 foram, respectivamente, 4,28; 3,00 e 2,75 pulgões predados para cada ovo gerado pelo predador.
Effect of cotton cultivars on biological aspects and predation behavior of Orius insidiosus (Say) preying on Aphis gossypii Glover.